PENYEGARAN KADER MEMPERSIAPKAN MASA MENOPAUSE YANG SEHAT DAN BAHAGIA: Entering Menopause: Stay Beautiful and Productive - Gustina, Irwanti; Handayani, Lutfi; Yuria, Mella (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Menopause is a natural stage in a woman's life characterized by the end of her menstrual cycle. Preparation for menopause is crucial to manage the physical, mental and emotional changes that may occur during this transition. This service activity aims to provide information to cadres in identifying important aspects in preparation for menopause as well as strategies that can help women deal with these changes. This activity also discusses efforts made to create a healthy and happy menopause so that every woman can understand the changes that occur in their bodies and deal with them better. The activity was held at the Pancoran mas community center in Depok.